2006
DOI: 10.1038/nchembio770
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic installation of thiols into sialic acid modulates adhesion and stem cell biology

Abstract: Metabolic 'oligosaccharide engineering' methods based on N-acetyl-D-mannosamine (ManNAc) analogs allow the glycocalyx of living cells to be remodeled. Herein we report the analog Ac(5)ManNTGc (1) that enables thiols to be expressed in surface sialic acids. By locating this versatile functional group on the outer periphery of normally nonadhesive human Jurkat cells, we obtained spontaneous cell-cell clustering and attachment to complementary maleimide-derivatized substrates. When analyzed in human embryoid body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
154
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(161 citation statements)
references
References 30 publications
3
154
0
4
Order By: Relevance
“…Many selective chemical probing techniques have been used for tagging glycoconjugates in cells. These methods include different bioorthogonal reactions such as ketoneaminooxy/hydrazide ligation (12,13), Staudinger ligation (14), Michael addition (15), and the strain-promoted, and Cu(I)-catalyzed [3 ϩ 2] azide-alkyne cycloaddition (16)(17)(18)(19). Many sugar analogs with small functional handles, including ketones and azides, are tolerated and have been incorporated into glycoconjugates (14,20,21).…”
mentioning
confidence: 99%
“…Many selective chemical probing techniques have been used for tagging glycoconjugates in cells. These methods include different bioorthogonal reactions such as ketoneaminooxy/hydrazide ligation (12,13), Staudinger ligation (14), Michael addition (15), and the strain-promoted, and Cu(I)-catalyzed [3 ϩ 2] azide-alkyne cycloaddition (16)(17)(18)(19). Many sugar analogs with small functional handles, including ketones and azides, are tolerated and have been incorporated into glycoconjugates (14,20,21).…”
mentioning
confidence: 99%
“…The azide group has been the most widely used reporter group due to its chemical stability, small size and bioorthogonal reactivity with alkynes and Staudinger phosphines. [12][13][14] Other chemical reporters used for metabolic labelling include: alkynes, 15,16 ketones, 17 thiols, 18 cyclopropenes 19,20 and alkenes. 21 We have recently shown that the isonitrile group can also be used as a novel chemical reporter group for glycan metabolic labelling.…”
Section: Introductionmentioning
confidence: 99%
“…The application of metabolic glycan engineering (MGE) using variants of natural monosaccharide analogs as precursors and their subsequent detection via orthogonal chemical reactions in vivo are opening up possibilities for glycan imaging (Laughlin and Bertozzi, 2009;Sletten and Bertozzi, 2009). Differential glycan profiling of glycan engineered cells (expressing azide, ketone, and thiol functionalities) using lectin microarrays might open up new possibilities for cell and tissue engineering including stem cell differentiation (Du and Yarema;Sampathkumar et al, 2006).…”
Section: Overview and Outlookmentioning
confidence: 99%